Physical exercise guideline to counteract the osteoarthrosis´s morning syntoms in the elderly - María Antonia Afre Socorro; Arelys de Armas Hernández; Danimary Labrador Afre; Yariel Gener Rodríguez; Yosniel Benitez Falero (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
Attention to the elderly is one of the priorities of the Cuban government. The research was carried out in the doctor´s office number 6 of Pinar del Río municipality. Theoretical methods were used (review of documents, inductive-deductive) and empirical methods (observation and interview) that made possible to deepen into the elderly characteristics, more common diseases, symptomatology and treatments, what confirmed that the elderly, when awakening, suffer from greater symptomatology in some diseases. Some guides of physical exercises were made to compensate this disorder, which are mainly based on joint mobility. The exercises are simple and easy to remember. Favorable results have been obtained according to the sample selected for the study, it was achieved pain relief and reduction of numbness, as well as undoubtedly a better day start with a favorable mood.